Seagrass Vegetation Analysis in Jhembengan and Pasir Putih Beach, Bawean Island, East Java - Muhammad Asmuni Hasyim; Bahrul Ulum; Berry Fakhry Hanifa (Biota, 2021)
Seagrass is a flowering plant that lives in coastal areas In Indonesia there are 12 species, where seagrasses are able to live at a depth of 1-90 meters, seagrass growth is influenced by several factors including the intensity of sunlight. The purpose of this study was to observe the cover, distribution, Importance Value Index (IVI) and correlation of abiotic factors with seagrass in Jhembangan Beach and White Sand on Bawean Island, East Java. The quadratic transect with 50 m length was used. Each station equipped with 3 transects with a distance of 25 m. The data collected includes the parameter of type, stand, and water quality. The data analyze use Past Program 3.15 systems. Three species of seagrass plant were collected. The total seagrass cover value was 32.6 percent at Jhembangan Beach, and 38 percent at Pasir Putih Beach. Clumped and uniform types were included in the distribution of seagrass at Jhembangan and Pasir Putih beach. The highest of important value index In Jhembangan and Pasir Putih was Thallasia hemprichii, while the association to abiotic factor such temperature, pH, salinity and DO variables are included in the good or perfect correlation with values range from 0.7 to 0.9.